Climate Services for Agriculture: Empowering Farmers to Manage Risk and Adapt to a Changing Climate in Rwanda (Final Project Report) - Hansen, James; Kagabo, Desire; Clarkson, Graham; Furlow, John; Fiondella, Francesco (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
A consortium of national and international partners worked from 2016 to 2020 to strengthen the climate information available to the Rwanda’s farmers and agriculture sector through the Rwanda Climate Services for Agriculture (RCSA) project, funded by the US Agency for International Development (USAID). It was launched at a workshop in Kigali on World Meteorological Day, March 23, 2016, with the goal to transform Rwanda’s rural farming communities and agricultural economy through improved climate services and climate risk management. Efforts towards this goal were organized around four target outcomes: 1. Climate services for farmers; 2. Climate services for government and institutions; 3. Climate information provision; and 4. Climate services governance. A final project evaluation used a mix of quantitative and qualitative analyses to assess the influence of the RCSA interventions, in particular PICSA and Radio Listeners Clubs (RLCs), on farmers’ awareness, access and use of climate information; and resulting welfare impacts. The quantitative evaluation was based on a survey of 1,525 farmers sampled from 15 districts. The qualitative component used 32 focus groups and 24 key informant interviews to provide deeper understanding of how women and men have used and benefitted from climate services as a result of project interventions.